Elderly Perceptions and Barriers in Accessing Digital Health Services: A Case Study in Tanjung Jaya Village, Panimbang District - Putra S, Deva; Okta Y, Setyo Luthfi (International Journal of Health, Medicine, and Sports, 2024)
In the era of rapid digitalization, digital health services such as telemedicine and health applications have become essential tools for improving healthcare access, especially for vulnerable groups like the elderly. However, older adults often face various challenges when attempting to access these services, including issues related to digital literacy, physical limitations, and concerns over data security. This study aims to explore the perceptions of elderly individuals in Tanjung Jaya Village, Panimbang District, towards digital health services and the barriers they encounter. Using a qualitative approach, in-depth interviews were conducted with 12 elderly participants who had experience with or knowledge of digital health services. The findings reveal that most participants have a neutral perception of digital health services, with some expressing concerns over the complexity of technology and the security of their personal data. The primary barriers identified include low digital literacy, physical limitations, and a lack of trust in digital platforms. Solutions suggested by participants include direct training, assistance from family or medical staff, and the development of elderly-friendly applications. These findings highlight the need for tailored support and more accessible, user-friendly digital health services for older adults to enhance their engagement and improve their health outcomes.